2016
DOI: 10.5194/gmd-9-161-2016
|View full text |Cite
|
Sign up to set email alerts
|

A fully coupled atmosphere–ocean wave modeling system for the Mediterranean Sea: interactions and sensitivity to the resolved scales and mechanisms

Abstract: Abstract. It is commonly accepted that there is a need for a better understanding of the factors that contribute to air-sea interactions and their feedbacks. In this context it is important to develop advanced numerical prediction systems that treat the atmosphere and the ocean as a unified system. The realistic description and understanding of the exchange processes near the ocean surface requires knowledge of the sea state and its evolution. This can be achieved by considering the sea surface and the atmosph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 35 publications
7
44
0
Order By: Relevance
“…CHAOS was selected since its atmospheric component offers advanced capabilities in simulating severe weather phenomena [48,[70][71][72][73]. The atmospheric component is two-way coupled with the ocean wave component through the OASIS3-MCT version 3.0 coupler [74] to better represent sea surface roughness which plays an important role in the atmospheric surface layer processes offering improvements in forecasting skill [48,[75][76][77]. The advantage of CHAOS is the capability to simulate hydrological processes using the WRF-Hydro version 3.0 [36] at defined drainage basins.…”
Section: Model Set Upmentioning
confidence: 99%
“…CHAOS was selected since its atmospheric component offers advanced capabilities in simulating severe weather phenomena [48,[70][71][72][73]. The atmospheric component is two-way coupled with the ocean wave component through the OASIS3-MCT version 3.0 coupler [74] to better represent sea surface roughness which plays an important role in the atmospheric surface layer processes offering improvements in forecasting skill [48,[75][76][77]. The advantage of CHAOS is the capability to simulate hydrological processes using the WRF-Hydro version 3.0 [36] at defined drainage basins.…”
Section: Model Set Upmentioning
confidence: 99%
“…The dramatic increase in computing power and the enhanced understanding of the physical processes responsible for wave generation, evolution, and dissipation have resulted in third-generation wave models which use first principles in the integration of an action or energy balance equation (Tolman, 1992) based on the sophisticated physics pertaining to wave generation, propagation, and decay mechanisms. Wave models like WAM (WAMDI Group, 1988;Komen et al, 1994), WAVEWATCH III (Tolman, 1991(Tolman, , 1999, and SWAN (Booij et al, 1999) are being used by many meteorological and oceanographic operational centres and have been reasonably successful in operational wave predictions at the global, regional, and coastal scales. One of the pioneers in the implementation and the development of wave analysis and forecast systems is the European Centre for Medium Weather Forecasts (ECMWF), which has provided daily medium-range global wave forecasts up to 10 days ahead since 1992.…”
Section: Introductionmentioning
confidence: 99%
“…Wind-wave models are very sensitive to wind field variations, which result in one of the main source of errors in wave predictions. The sensitivity of wave model prediction to variations in wind forcing fields has been studied by several authors (Komen et al, 1994;Teixeira et al, 1995;Holthuijsen et al, 1996;Ponce and Ocampo-Torres, 1998). This is particularly true for the Mediterranean where the limited contribution of swell to the wave spectrum makes the regional wind conditions the most important factor in determining the local wave state.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of both methods by Moghimi et al (2013) showed that the results are similar for longshore circulations, but radiation stress enhanced offshore-directed transport in wave shoaling regions. Many other studies addressed the role of the interaction between wind waves and circulation in the model simulations (Michaud et al, 2012;Barbariol et al 2013;Brown et al, 2011;Katsafados et al, 2016;Bolaños et al, 2011Bolaños et al, , 2014Röhrs et al, 2012).…”
Section: Introductionmentioning
confidence: 99%